Long-term outcomes associated with participation in school-based extracurricular activities for at-risk adolescents - Montoya, Andrea L., author; Rosén, Lee A., advisor; Suinn, Richard M., committee member; Henry, Kimberly L., committee member; Butki, Brian D., committee member (Colorado State University. Libraries, 2012)
The current study sought to explore the long-term outcomes associated with participation in extracurricular activities for at-risk adolescents. Participation was divided into four categories; sports, non-sports, multiple (sports and non-sports), and no activity. Psychological, educational/economic, and deviant behavior outcomes were measured, and the major conclusion that emerged from was that participation in high school extracurricular activities (especially multiple activities, including both sports and non-sports activities) was associated with a number of positive long-term effects in a variety of domains. With a few notable exceptions that deserve further inquiry, participation in high school extracurricular activities appeared to be beneficial for at-risk youth and should be encouraged by parents, in the way of modeling, verbal praise and encouragement, financial resources, time, etc., and by communities, in the way of funding, opportunities for low-cost activities, and through the promotion of an active/involved lifestyle starting in childhood.